Moving beyond Discontinuity in Religious Conversion in Africa: A Preface to the Special Issue - Bruner, Jason ca. 20./21. Jh. (Religions, 2020)
This Special Issue emerged through a conversation about how to foster new lines of analysis with respect to religious, cultural, and social change on the African continent [...]